Laws and Acts of Her Majesties Colony of Rhode Island, and Province-Plantations Made from the First Settlement in 1636 to 1705, at 48 (1896) - (:unkn) unknown (My University, 1700)
Persons subject to militia service also had to serve on watch and ward (day and night guard duty in towns). Mandated that each militiaman appear with a "Good & Sufficient muskett or Fuze a Sword or Bayenet, Catooch box or Bandelers wth twelve Bulets fit for his Piece half a Pound of Powder & Six good Flints."
Keywords: MILITIAS; REQUIRED POSSESSION